Health Benefits of Phyto-oestrogens – A Consensus Review - Sunita, P.; Jha, S.; Pattanayak, S.P. (Pharmacognosy Reviews)
This paper brings up regarding the plant derived compounds with estrogenic activity. The authors correctly emphasize the need for control of estrogenicity of foods containing phyto-oestrogens in view of the significant health effects of various estrogenic derivatives. This is particularly essential in the light of the current wave of enthusiasm for vegetarian food in general and phytooestrogens in particular. Phytoestrogens are plant-derived hormone-like diphenolic compounds of dietary origin that are present at high levels in plasma of healthy subjects. These compounds are weakly estrogenic and appear to influence the hormone dependent cancers (breast cancer, prostate cancer), viral infection, atherosclerosis, chronic heart diseases and osteoporosis, besides that the review concludes with the discussion of the effects of phyto-oestrogen on reproductive system, neuroprotective effect, retinal thickness, dementia and alcohol metabolism.
Keywords: Phyto-oestrogen; health effects; vegetarian food